2013
DOI: 10.4103/2249-4847.116409
|View full text |Cite
|
Sign up to set email alerts
|

Salmonella paratyphi B septicemia in a neonate

Abstract: Septicemia is a major cause of death in neonates especially in developing countries. We report a case of septicemia in a neonate due to Salmonella Paratyphi B. The baby responded well to therapy and recovered completely.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 4 publications
(5 reference statements)
0
1
0
Order By: Relevance
“…In the second case report, by Mohanty et al in 2009 [ 3 ], the preterm neonate was shown to be blood culture positive for S. enterica Paratyphi A and the baby survived, but the mother’s blood and stool cultures were negative for Salmonella ( Table 1 ). In another case study, vertical transmission of S. enterica Paratyphi B was reported from South India [ 17 ].…”
Section: Discussionmentioning
confidence: 99%
“…In the second case report, by Mohanty et al in 2009 [ 3 ], the preterm neonate was shown to be blood culture positive for S. enterica Paratyphi A and the baby survived, but the mother’s blood and stool cultures were negative for Salmonella ( Table 1 ). In another case study, vertical transmission of S. enterica Paratyphi B was reported from South India [ 17 ].…”
Section: Discussionmentioning
confidence: 99%